Work-Life Balance and Its Impact on Employee Retention in the Indian Manufacturing Industry: Assessing the Mediating Role of Job Satisfaction and Organizational Culture - Singh Rana, Surendra (Digital Repository of Theses, 2026)
In today’s dynamic and highly competitive business environment, employee retention has become a critical concern, especially in sectors like manufacturing that rely heavily on skilled and experienced labor. The present study aims to examine the relationship of work-life balance (WLB) to employee retention (ER) in the manufacturing sector in India considering job satisfaction (JS) and organizational culture (OC) as mediating factors. This research is based on well-set theoretical foundations like Role Theory, Social Exchange Theory, and Job Embeddedness Theory. It aims at fine-tuning of knowledge onto how employee-centered practices at workplaces impact retention outcomes. They take a quantitative methodology through Structural Equation Modeling (SEM) via SmartPLS to validate the proposed conceptual framework. 392 employees were given a structured questionnaire from different regions and hierarchical levels under the manufacturing sector. The data tested rigorously for reliability and validity of the study employing Cronbach alpha, composite reliability, average variance extracted (AVE), and outer loadings, with the Fornell-Larcker Criterion and HTMT ratio verifying discriminant validity, while collinearity diagnostics and model fit indices confirming robustness. The results show a strong positive relationship between work-life balance and job satisfaction as well as organizational culture. In addition, both job satisfaction and organizational culture predict employee retention significantly. Furthermore, there is a direct positive relationship between work-life balance and retention, although weaker than other indirect relationships. Mediation analysis supports that both job satisfaction and organizational culture serve partial mediators of the relationship between work-life balance and employee retention. Hence, such dual mediation reflects the psychological and organizational mechanisms that undergird through which work-life initiatives culminate into sustained employee commitment. Theoretically, this research adds to the growing literature on organizational behavior by combining a number of constructs into one empirical model. It thus validates that policies on work-life are relevant, not only in the improvement of individual well-being but also in the development of organizational culture and enhancement of retention strategies. Practically, the study makes recommendations for HR managers and policymakers regarding what should be put in place. Those include institutionalizing flexible work arrangements and developing a supportive workplace culture as well as investing in job enrichment strategies that would improve employee satisfaction and loyalty. This research, above everything, admits that work-life balance is not just a temporary advantage but a strategic driving force for sustainability in organizations. By putting employee well-being right in the middle of workplace policies, an organization will build stronger frameworks for retaining talent in the current industrial transformational journey through India’s manufacturing sector amidst ever-increasing pressures in the country. Keywords: Work-Life Balance (WLB), Job Satisfaction, Organizational Culture, Manufacturing Sector Employees, Structural Equation Modeling (SEM)